2014
DOI: 10.1186/scrt508
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-chondroitin-6-sulfate-hyaluronic acid scaffold seeded with vascular endothelial growth factor 165 modified hair follicle stem cells as a three-dimensional skin substitute

Abstract: IntroductionIn the field of skin tissue engineering, gelatin-chondroitin-6-sulfate-hyaluronic acid (Gel-C6S-HA) stents are a suitable bio skin substitute. The purpose was to investigate the effect of genetically-modified hair follicle stem cells (HFSCs), combined with Gel-C6S-HA scaffolds, on the vascularization of tissue-engineered skin.MethodsThree-dimensional (3D) Gel-C6S-HA scaffolds were prepared by freeze-drying. Vascular endothelial growth factor (VEGF) 165 gene-modified rat HFSCs (rHFSCs) were inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Chondroitin sulfate, one of the major components of cartilage ECM, has important therapeutic properties, such as anti‐inflammatory effects while promoting wound healing by increasing cellular adhesion and proliferation during the healing process . To benefit from these properties, chondroitin sulfate has been combined with gelatin and HA for developing 3D scaffolds for cartilage tissue engineering and skin substitutes . Addition of chondroitin sulfate to gelatin improved the resistance against collagenase‐induced degradation, preserving the storage modulus and porosity of gelatin, while HA promoted the integration of engineered cartilage with the host tissue and improved the scaffold strength.…”
Section: Gelatin–polysaccharides Composites In Cell Culture and Tissumentioning
confidence: 99%
“…Chondroitin sulfate, one of the major components of cartilage ECM, has important therapeutic properties, such as anti‐inflammatory effects while promoting wound healing by increasing cellular adhesion and proliferation during the healing process . To benefit from these properties, chondroitin sulfate has been combined with gelatin and HA for developing 3D scaffolds for cartilage tissue engineering and skin substitutes . Addition of chondroitin sulfate to gelatin improved the resistance against collagenase‐induced degradation, preserving the storage modulus and porosity of gelatin, while HA promoted the integration of engineered cartilage with the host tissue and improved the scaffold strength.…”
Section: Gelatin–polysaccharides Composites In Cell Culture and Tissumentioning
confidence: 99%
“…For instance, Perng CK et al cultured adult human bone marrow MSCs on gelatin scaffold with pNIPAAm as transplanted grafts for skin regeneration which could increase the re-epithelialization markers of human pan-cytokeratin and E-cadherin and decrease the stem cell markers of human CD13 and CD105 during the period of wound healing [59]. In another study, gelatin-chondroitin-6-sulfate-hyaluronic acid scaffold was seeded with VEGF-165 modified hair follicle stem cells as a three-dimensional skin substitute [60]. Xu K et al utilized thiol-ene Michael-type addition for rapid encapsulation of MSCs within a gelatin/poly (ethylene glycol) biomatrix, which facilitated better function of MSCs in rat skin wound [61].…”
Section: Discussionmentioning
confidence: 98%
“…45 Previous studies showed that if integrated with other natural compounds, aminoacids, minerals, and various antioxidant compounds, it improves cutaneous aging-induced wrinkles 36 and stimulates hair follicles stem cells. 46 In fact, chondroitin sulfate binds and modulates the functions of a large number of biomolecules involved in hair follicle differentiation or proliferation, 47 including fibroblast growth factors (FGFs), 48 vascular endothelial growth factor (VEGF), 49 sonic hedgehog, 50 bone morphogenetic proteins (BMPs), 51 Wnt 50 and hepatocyte growth factor (HGF).…”
Section: Discussionmentioning
confidence: 99%